Novel identification of biofluids using a multiplex methylation sensitive restriction enzyme-PCR system. (November 2016) - Lin, Yu-Chih; Tsai, Li-Chin; Lee, James Chun-I; Su, Chih-Wen; Tzen, Jason Tze-Cheng; Linacre, Adrian; Hsieh, Hsing-Mei
Graphical abstract: Highlights: A new 10-plex MSRE-PCR system was established to identify the body fluids of venous blood, semen, saliva, vaginal fluids and menstrual blood. The validation of the 10-plex MSRE-PCR system showed that 0.25 ng DNA was sufficient to obtain reproducible identification of biofluid types. The MSRE-PCR system and AmpFlSTR ® MiniFiler™ were co-amplified in a single reaction to generate both biofluid and miniSTR profiles. Abstract: The identification of a specific body fluid encountered in a forensic investigation can give crucial information. This identification can be aided by methylation profiles based on selected markers specific to a range of biofluids. In this study, the open database of Infinium HumanMethylation450 BeadChip was searched for markers specific for semen, vaginal fluids, saliva, venous blood and menstrual blood. A total of 8 biofluid-specific methylated markers and 2 control markers were combined into a 10-plex methylation sensitive restriction enzyme-PCR (MSRE-PCR) system. Based upon the analysis of 100 DNA samples from these 5 biofluid types, unambiguous results were obtained to identify the body fluid from which it originated. Validation studies of the developed 10-plex MSRE-PCR included sensitivity, reproducibility and mixed body fluids. Co-amplification of the established MSRE-PCR system and the microsatellite loci in AmpFlSTR ® MiniFiler™ PCR Amplification Kit was performed to generate both the methylation profile for biofluid type and the miniSTR profile. This allowed human identification and the identification of the body fluid type to be performed in a single reaction. The results of this study displayed the applicability of this 10-plex MSRE-PCR system in forensic science.